Philosophy of romantic opera, women problem and European nation formation in the XIX century - Sharov, Konstantin S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Romantic opera is an operatic genre whose emergence and development coincided with the active processes of building a national picture of Europe. The connection between the work of operatic composers and activities of national political elites in the emerging European nations, primarily German and Italian, is known. The purpose of this paper is to find out the role of the Romantic opera tradition in the formation of gender national narratives of the XIX century, specific for the creation of Italian and German nations. In this article, for the first time, the gender mechanisms of socio-political influence of Romantic opera on the European society of the XIX century, is examined. It is showed that the incredible success of Romantic opera as a mechanism of national building can be explained mainly by the fact that music and narrations of Romantic operas, unlike previous genres, significantly utilised the gender theme. For this reason, they were successfully accepted by women. This fact enabled national theoreticians and political elites in Italy and Germany to incorporate the gender dimension into their national programmes using the romantic Opera as a tool for the creation of emerging national communities. The support of the female part of their societies was secured on an equal basis with the male part by the direct influence of Romantic opera on the Italian and German cultures.
Keywords: philosophy of music; nation; nationalism; gender problem; symbolism